Humic Acid Isolation from Batujai Dam Lombok Tengah-NTB and its Potential as Reductive–Biosorbent Au(III) in The Batch System - Ismillayli, Nurul; Hermanto, Dhony (Jurnal ILMU DASAR, 2020)
The Study of Au(III) ions adsorption by humic acid in batch system has been done. Humic acid was isolated from Batujai Dam Lombok Tengah 0.1 M NaOH and continued with 0.1 M HCl/0.3 M HF washing to dissolve silica. Functional groups of isolated humic acid was investigated by FTIR Spectroscopy and the adsorption process was studied by XRD and SEM analyses. It has been found that humic acid contained carboxylic, phenols, alcoholic, ether, amines functional groups, aliphatic hydrocarbon and aromatic ring. XRD and SEM data showed that humic acid did not only adsorp Au(III) ions but also reduce them to gold particles. Therefore, humic acid has the potential as reductive-biosorbent for Au(III) in batch system. Keywords: humic acid, reductive-biosorbent, Au(III) ions.